Optimization of eIF4E-Binding Peptide Pep8 to Disrupt the RBM38-eIF4E Complex for Induction of p53 and Tumor Suppression - Lucchesi, Christopher A.; Zhang, Jin; Vasilatis, Demitria M.; Yip, Elizabeth; Chen, Xinbin (Frontiers in Oncology, 2022)
Interaction of RNA-binding protein RBM38 with eIF4E on p53 mRNA is known to suppress p53 mRNA translation, which can be disrupted by an 8-amino acid peptide (Pep8-YPYAASPA) derived from RBM38, leading to induction of p53 and tumor suppression. Here, we rationally designed multiple Pep8 derivatives and screened for their binding affinities towards eIF4E in silico. We showed that several key residues within Pep8 are necessary for its structure and function. We identified a shortened 7-amino acid peptide (Pep7¬-PSAASPV) that has the highest affinity towards eIF4E and is the most potent inducer of p53 expression. We found that iRGD is an effective vehicle to deliver Pep7 inside of cells for induction of p53 expression and growth suppression as compared to other cell penetrating peptides (Penetratin and Pep-1). We found that peptide cyclization enhances Pep8 affinity for eIF4E and induction of p53. We also found that the ability of Pep7 to induce p53 expression and growth suppression is conserved in cells derived from canine osteosarcoma, a spontaneous tumor model frequently used for testing the feasibility of a therapeutic agent for human cancer. Moreover, we showed that both human and canine osteosarcoma cells, which are notoriously resistant to radiation therapy, were sensitized by Pep7 to radiation-induced growth suppression and cell death. Together, our data suggest that Pep7¬ may be explored to sensitize tumors to radiation therapy.